Aortic valve calcification and risk of stroke: A systematic review and meta-analysis. (September 2018) - Zhang, Danfeng; Dai, Xianliang; Wang, Chaoqun; Han, Kaiwei; Wang, Junyu; Dong, Yan; Chen, Jigang; Hou, Lijun
Highlights: The relationship between AVC and stroke was investigated by a meta-analysis. Significant correlation between AVC and stroke was detected with low heterogeneity (RR, 1.20; 95% CI, 1.02–1.40, P = 0.02). Subgroup analysis indicated no significant results in all subgroups except one group. The relationship between AVC and risk of stroke couldn't be determined based on current available studies. Abstract: Aortic valve calcification (AVC) is common among aged population and reported to be associated with the risk of stroke. However, the conclusions are inconsistent among studies. We performed a rigorous meta-analysis to unravel the AVC-stroke relationship. Embase, PubMed and Cochrane library were retrieved for related cohort studies investigating the correlations between AVC and risk of stroke. The language was limited to English. We selected risk ratio (RR) and 95% confidence intervals (CIs) as the effect size. Random-effects model was used in the data synthesis. A total of 7 cohort studies were identified in our meta-analysis with 21, 395 participants and 1025 strokes. We detected statistically significant correlation between AVC and stroke (RR, 1.20; 95% CI, 1.02–1.40, P = 0.02) with low heterogeneity ( I 2  = 6.9%, P = 0.375). Statistically significant results were detected only in the subgroup of "+" degree of adjustment (P = 0.04). Therefore, a definite relationship between AVC and risk of stroke couldn't be decided based on current available data, and more large scale prospective studies were needed to verify the AVC-stroke relationship.